PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM DESA TANGGUH BENCANA DI KABUPATEN KUTAI KARTANEGARA - Arwanto Harimas Ginting; Tri Dewi Wijayanti (Institut Pemerintahan Dalam Negeri, 2019)
Empowering communities through the Resilient Disaster Village Program in Kutai Kartanegara Regency, East Kalimantan Province is an important study, to improve the ability, knowledge, and independence of the community in dealing with and overcoming disaster problems. The research method in this study is a descriptive research method with an inductive approach. Meanwhile, data collection techniques are semi-structured interviews, observation, and documentation. The author analyzes the data, through processes namely, data reduction, data presentation, and conclusion drawing. The results of observations on the implementation of Community Empowerment, through the Resilient Disaster Village Program, have been going well. This is influenced by supporting factors in the implementation of this program, namely community participation, contributions of implementing activities and cooperation between related parties. The inhibiting factors for program implementation are limited community time and a budget that does not exist every year. The author advises stakeholders to become a sustainable program (sustainable), increase the number of Tangguh Bencana Village and add facilitators, and the community needs to take control in the form of anticipation and disaster management.